A case of peeling skin syndrome - Anil K Singhal; Devendra K Yadav; Bajrang Soni; Savita Arya (Wolters Kluwer Medknow Publications, 2017)
Peeling skin syndrome is a very rare autosomal recessive disease characterized by widespread painless peeling of the skin in superficial sheets. Etiology is still unknown with an autosomal recessive inheritance. Less than 100 cases have been reported in the medical literature. We present a 32-year-old man having asymptomatic peeling of skin since birth. Sheets of skin were peeling from his neck, trunk, and extremities, following friction or rubbing especially if pre-soaked in water but sparing palm and soles. Histologically, there was epidermal separation at the level of stratum corneum, just above the stratum granulosum. This case is being presented due to its rarity.